Quantifying the Disparity in Vehicular Carbon Emissions and Sequestration Capacity in Urban Environments via E-cognition and Primary Data Analysis: A Case Study of Bhopal, Madhya Pradesh - Vibhor Bhardwaj; Greeffin Raju Fule; Surabhi Mehrotra (Calibrating Urban Livability in the Global South, 2024)
India is now the 3rd largest emitter of greenhouse gases in the world, with around 7.3% share of its name, with many of these gases originating in urban areas. Urbanization has led to the overtake of open and green spaces by road networks and built-up areas which have resulted in the elevation of many climate threats like urban heat islands and severe impacts on urban livability. Policies on mitigating the carbon footprint of big cities are being developed, and one of the measures is promoting urban parks and greenery to offset net greenhouse gas emissions. Studies show that urban greenery can work as a carbon reservoir and enhance the livability index of urban areas, but support for such claims and their efficacy is still lacking. This study is devised to check the efficiency and potential of green spaces, urban parks and trees in sequestering CO2 directly from the atmosphere and removing other pollutants present in an urban environment. Taking a zoned-out area demarcating some wards for Bhopal, Madhya Pradesh, with variable traffic volume and different green cover, as a case, the authors integrated various methods to estimate carbon emissions, their impact, and sequestration. This study involves the use of E-cognition for object recognition using high-resolution satellite imagery. The methodology will involve various analyses initiating from traffic volume survey for vehicular carbon emissions analysis, followed by, the calculation of carbon sequestration based on object recognition and conduction of physical surveys to identify the biomass and various species of trees present. This study focuses on the gap analysis between the vehicular carbon emissions and carbon sequestration capability of the trees. Furthermore, understanding how urban greenery helps reduce emissions and its effects while elevating the social and ecological environment of urban spaces further elevating urban livability. The study’s findings can also guide policymakers and stakeholders in implementing effective carbon-offset strategies through parks and urban afforestation. Furthermore, studies can be done to reduce carbon emissions and urban heat island formation on road networks, by making them more manageable.